Efektifitas senam hamil terhadap penurunan nyeri punggung pada ibu hamil - Yosefa, Febriana -; -, Misrawati -; Hasneli, Yesi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this research was to determine the effectiveness of pregnancy exercise for reduction back pain during pregnancy. The method of this research was quasi- experimental and used non- equivalent control group as the research design. This research was conducted at Puskesmas Karya Wanita Pekanbaru that consist of 30 people, 15 people were experimental group and 15 people were control group. The total sample are 30 people who were taken by using purposive sampling techniques by noticing to the inclusion criteria. The analysis that was used in this research were univariate and bivariate analysis with used wilcoxon test and t-independent test. The results showed there was a significant reduction of back pain during pregnancy in experimental group has given pregnancy exercise with p value 0,001 (<0,05). It means that pregnancy exercise is effective for reduction back pain during pregnancy. The result of the research is recommend for public health center to organize prenatal class especially pregnancy exercise regularly Keywords: back pain, pregnancy exercise, pregnancy